New players, new game? : the impact of emerging economies on global governance - Jong, Sijbren de (Amsterdam : Amsterdam University Press, 2012)
How have emerging economies, such as Brazil, Russia, India, China, South Africa, as well as Indonesia, Turkey and South Korea (or'BRICS+'), affected the international power balance? And to what extent are these countries cooperating strategically on economic, diplomatic, and security matters? The contributors to 'New Player, New Game' consider the potential for the BRICS+ to fuel the emergence of a bipolar world of 'the West against the Rest,' thus potentially leading to an increased cost of doing business, reduced chances of promoting human rights, increased diplomatic and military tensions, and a decrease in economic globalization.
Title from publisher's bibliographic system (viewed on 22 Feb 2021).
Keywords: International economic relations; BRIC countries -- Foreign economic relations; BRIC countries -- Foreign relations; Developing countries -- Foreign economic relations; Developing countries -- Foreign relations; Developing countries -- Economic conditions